Jekyll and Heidi - Stine, R. L. (New York : Scholastic, 1999)
Heidi, orphaned when her parents are killed in a car accident, discovers that her Uncle Jekyll is half human and half beast.
"An Apple paperback."
"A Parachute Press book"--T.p. verso.
4.0
3-6.
Keywords: Monsters -- Fiction; Uncles -- Fiction; Orphans -- Fiction; Horror stories; Monsters -- Fiction; Uncles -- Fiction; Orphans -- Fiction; Horror fiction